Analysis of The Effectiveness of The Management of The Village Income and Expenditure Budget (APBDes) in Lembantongoa Village - M. Marsanda; Andi Herman Jaya; Edhi Taqwa; Yunus Sading; M. Musdayati (Golden Ratio of Data in Summary, 2024)
This study aims to assess the effectiveness of the management of the Village Revenue and Expenditure Budget (APBDes) for Stages 1 and 2, which covers the period from January to August 2023 in Lembantongoa Village, Palolo Sub-district, Sigi Regency. The research method applied is a qualitative approach with a descriptive methodology. The study uses two types of data: primary and secondary data, collected through interviews and observations. The subject of this research is Lembantongoa Village, Palolo Sub-district, Sigi Regency. The results of the study include the calculation of the effectiveness ratio for APBDes management in Lembantongoa Village for the year 2023. Among the five activity fields listed in the APBDes of Lembantongoa Village, Palolo Sub-district, Sigi Regency, none are categorized as effective, and only one field is categorized as moderately effective, with an effectiveness rate of 86% in the Empowerment field, while the other fields are classified as less effective, with effectiveness rates ranging from 66-75%. To improve the management of village funds, the Lembantongoa Village Government conducts village deliberations aimed at developing a Village Government Work Plan (RKPDes) that addresses the needs of the community. Through these deliberations, it is hoped that the planned development activities can be effectively implemented. Additionally, it is expected that the Lembantongoa Village Government will conduct training to enhance the capacity of village apparatus so that they can perform their duties and functions more effectively.